2022
DOI: 10.48550/arxiv.2205.11968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noise-driven bifurcations in a nonlinear Fokker-Planck system describing stochastic neural fields

Abstract: The existence and characterisation of noise-driven bifurcations from the spatially homogeneous stationary states of a nonlinear, non-local Fokker-Planck type partial differential equation describing stochastic neural fields is established. The resulting theory is extended to a system of partial differential equations modelling noisy grid cells. It is shown that as the noise level decreases, multiple bifurcations from the homogeneous steady state occur. Furthermore, the shape of the branch at a bifurcation poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We also remark that the Fokker-Planck PDE (1.4), in the case of diffusion term σ " σ 0 constant, has been further analyzed in [12,13]. Under particular assumptions on the drift term, it is shown that for every noise strength σ 0 ą 0 there exists a unique stationary space homogeneous solution (from the modelling point of view this corresponds to the animal completely loosing track of its position in space).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also remark that the Fokker-Planck PDE (1.4), in the case of diffusion term σ " σ 0 constant, has been further analyzed in [12,13]. Under particular assumptions on the drift term, it is shown that for every noise strength σ 0 ą 0 there exists a unique stationary space homogeneous solution (from the modelling point of view this corresponds to the animal completely loosing track of its position in space).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, as the brain is inherently noisy, understanding how the grid cell network is affected by noise is one of the currently open challenges in the field. This question has recently been addressed from several directions [7,9,10,23,26,31,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation